The prevailing organizational culture in schools of education in Jerash Governorate and its relationship to the job integration of teachers - الزبون آيات; محمد الحراحشة; محمد بني خالد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study aimed to identify the level of organizational culture prevailing in schools of education in Jerash Governorate and its relationship to the job integration of teachers. The study relied on the descriptive, correlational survey method. The study sample consisted of (367) teachers, including (165) males and (202) females, and they were selected. By random method and by (10%) of the study population, the results of the study showed: The level of organizational culture prevailing in the schools of education in Jerash Governorate from the point of view of teachers was rated highly, and there were no statistically significant differences attributed to the variables of gender, years of experience, and academic qualification in all fields. In the total grade, there were statistically significant differences attributed to the variable of the academic stage in all areas, and in the total grade, the differences were in favor of the basic stage. The results of the study showed that the level of functional integration in the schools of education in Jerash Governorate from the point of view of teachers was highly rated, and there were no significant differences. Statistical significance in job integration is attributed to the variables of gender, years of experience, and academic qualification in all fields and in the total grade, and the presence of statistically significant differences at the level of significance attributed to the variable and academic stage in all fields and in the total grade. The differences were in favor of the basic stage, and the presence of a statistically significant positive relationship between The level of organizational culture prevailing in schools of education in Jerash Governorate and the level of job integration among teachers from their point of view. Based on the results of the study, the researcher recommends maintaining the high level of organizational culture and job integration of teachers in schools of education in Jerash Governorate.